An Analysis of Grammatical Errors in Students’ Writing: A Case Study of Economics Department Students Batch 2022 Class E - Sri Ani Puji Setiawati (Syntax Corporation, 2022)
Writing is regarded as the most difficult skill to acquire because, according to Harmer (2004:31) cited in Wati & Nursyaebah (2017), learners frequently have more time to reflect when writing than they do during spoken activities. In order to help them, students can use dictionaries, grammar books, and other reference materials to help them activate their brains. He advised consulting grammar books to ensure that the work was grammatically correct because he thought grammar was crucial in writing. As a result, the main goal of this research is to examine students' writing, particularly their grammatical errors. The six categories of grammatical errors are verb agreement (Leech, 1985), capitalization (Oshima, 1988), use, sentence structure (Ross, 1975), pronoun and spelling (Brooks, 1964), according to Wati and Nursyaebah (2017). Based on student writing mistake analyses, the data were examined. According to the research findings, students usually made mistakes with verb agreement (34.8%), which they accomplished by employing the wrong form of the simple present. They also frequently made mistakes with capitalization (17.4%), spelling (17.4%), usage (13%), sentence structure (8.7%), and pronoun errors (8.7%). As a result of the findings, it is recommended that teachers revisit their lessons on verb agreement, capitalization, and spelling, which are the three areas where pupils consistently fail when writing.